Effects Of Trade Facilitation Measures On Gdp, Exports And Imports In Developing Countries - Al Farajat, Marwan Hweishel A. (2024)
This study delves into the impact of trade facilitation measures on the economic development of developing nations, with a specific focus on their influence on GDP, imports, and exports. Utilizing secondary data from 40 developing countries spanning the period from 2015 to 2019, the research employs the rigorous Generalized Method of Moments (GMM) estimation in Stata 16 to analyze 11 key variables. The results reveal the positive effects of well-structured trade facilitation measures that align with contemporary best practices, particularly in the domains of Publication and Availability of Information, Opportunity to Comment, Information Before Entry Into Force and Consultations, Formalities Connected with Importation, Exportation, and Transit, and Automation.